Integrating East Nusa Tenggara's Local Wisdom into Project-Based Learning to Assess Students' Concept Comprehension, Crucial Learning Skills, and Attitudes Towards Chemistry Learning - Tinenti, Yanti Rosinda; Dasna, I Wayan; Habiddin, Habiddin; Munzil , Munzil; Tangi, Hironimus; Moreira, Ilidio X. (Universitas Negeri Semarang, 2025)
This research aims to analyze the strategies employed in the implementation of Chem-PjBL-L-NTT-W (the Integration of NTT local wisdom in PjBL for chemistry), their effects on crucial learning skills (CLS), attitudes toward chemistry learning (ATCL), and comprehension of concepts. An investigation into students' perspectives and the difficulties encountered by teachers during implementation has been undertaken. A quantitative and qualitative research study with a one-group pretest-posttest design was employed. Paired t-test and Wilcoxon signed-rank test were used based on the normality of the data obtained by the Kolmogorov-Smirnov test. The results showed that the implementation strategy of the Chem-PjBL-L-NTT-W model was carried out through the identification and integration of the characteristics of chemistry materials with NTT local wisdom, along with the determination of three project themes for each learning material. The implementation of this model has a significant effect on CLS and ATCL, with variations in effects based on the school context. The effect on CLS was strong for senior high school students in the TTS regency, moderate in the Belu regency, and statistically significant but with a very small effect in the TTU regency. Regarding the ATCL aspect, there was a significant and strong effect in TTS, but the practical improvement was relatively minimal. In contrast, in Belu, the effect was very small and inconsistent. Students' concept comprehension in all three regencies showed significant improvement, with a range of confidence intervals indicating meaningful practical effects. Geographical location, facility and infrastructure availability, teacher readiness, school policies, and student interest have been recognized as critical determinants.